MENINGKATKAN KEMAMPUAN MENCUCI PAKAIAN MELALUI ANALISIS TUGAS PADA ANAK TUNAGRAHITA SEDANG - Sari Kurniawati (Universitas Negeri Padang, 2015)
This research was conducted based on the problem found in the field indicating that a student with light mental retardation X got problem to wash his clothes. The purpouse of this research was to increase the student’s ability to wash clothes though task analysis in class IV C1 of SLB Fanredha Padang. This was a Single Subject Research which used A-B design. A condition (baseline condition) was the initial contion showing the student’s ability to wash clothes before the treatment given. B condition ( intervention condition) was the condition through which the task analysis was applied. The result of the research indicated that the ability of the studen with light mental reterdation to wash clothes increased after the task analysis given. In the baseline condition, six observasions were conducted. In this condition the highest score was 35%. In the intervention condition that consited of ten observations, the highest score of the student was 90%. Thus, it was revealed that task analysis could increase the ability of the student with light mental retardation X to wash clothes in class IV/C1 of SLB Fanredha Padang. The researcher suggested to the teachers to use task analysis to help the students to wash their own clothes. Kata kunci: analysis tasks; Washing Clothes.